2018
DOI: 10.1016/j.celrep.2018.05.078
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Regulate Sleep and Sleep Homeostasis in Drosophila

Abstract: SUMMARY To discover microRNAs that regulate sleep, we performed a genetic screen using a library of miRNA sponge-expressing flies. We identified 25 miRNAs that regulate baseline sleep; 17 were sleep-promoting and 8 promoted wake. We identified one miRNA that is required for recovery sleep after deprivation and 8 miRNAs that limit the extent of recovery sleep. 65% of the hits belong to human-conserved families. Interestingly, the majority (75%), but not all, of the baseline sleep-regulating miRNAs are required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…In conclusion, consistent with prior animal experiments suggesting distinct roles for miRNAs in sleep-wake regulation and aging [14,15,17,[24][25][26][27][28], we here report for the first time that wakefulness and sleep affect the blood miRNA expression profile in young and older men. Given the rather small study sample, the reported results need to be considered preliminary.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In conclusion, consistent with prior animal experiments suggesting distinct roles for miRNAs in sleep-wake regulation and aging [14,15,17,[24][25][26][27][28], we here report for the first time that wakefulness and sleep affect the blood miRNA expression profile in young and older men. Given the rather small study sample, the reported results need to be considered preliminary.…”
Section: Discussionsupporting
confidence: 92%
“…A new line of research has recently linked miRNAs with sleep-wake regulation. More specifically, studies in Drosophila suggested that distinct miRNAs, particularly let-7, control the structure and amount of sleep, in addition to the sleep-wake dependent (i.e., homeostatic) aspect of sleep-wake regulation [17]. Sleep deprivation is the most pronounced physiological challenge of sleep homeostasis and drastically alters the blood proteome in animals and humans [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…New epigenetic mechanisms regulating sleep are emerging, with several investigations showing that some miRNAs are related to circadian control (Goodwin et al., ). In our study, computational predictions suggest that selected miRNAs are potentially associated with the circadian rhythm in humans.…”
Section: Discussionmentioning
confidence: 99%
“…MiRSPs offer the ability to dissect the role of individual miRNAs with both spatial and temporal precision (Ebert and Sharp 2010;McNeill and Van Vactor 2012). The efficacy of this technique has been demonstrated in a number of studies in Drosophila and other species (Loya et al 2009;Bejarano et al 2012;Pathania et al 2012;Li et al 2013;Loya et al 2014;Lu et al 2014;Busto et al 2015;Fulga et al 2015;Mugat et al 2015;Goodwin et al 2018). More comprehensive comparison of adult viability phenotypes detected using our expanded toolkit of miR-SPs with data from similar screens of null alleles (Chen et al 2014) also shows that lethal phenotypes are rare and that miR-SPs recapitulate the vast majority of null phenotypes .…”
Section: Microrna Motor Behavior Drosophila Melanogastermentioning
confidence: 79%